Peningkatan Kepercayaan Diri dan Pengurangan Kecemasan Masa Depan melalui Konseling Eksistensial: Studi Kasus Kualitatif pada Mahasiswa - Nuryono, Wiryo; Ratnasari, Devi; Khofifah, Dhiya; Hasnabila Firjatullah, Talitha (Universitas Palangka Raya, 2026)
Self-confidence is an essential aspect of psychological well-being but is often undermined by fears about the future, particularly among university students undergoing identity formation. This study explores the effectiveness of existential counseling in enhancing self-confidence and reducing future-related anxiety in a student experiencing an identity crisis due to academic, social, and intrafamilial pressures. Using a qualitative case study design, one purposively selected participant took part in the study. Data were collected through in-depth interviews, observations, and counseling session documentation, then analyzed using content analysis to identify themes related to behavioral change, emotional regulation, and the courage to act authentically. The results revealed three main findings: (1) low self-confidence was triggered by negative social comparisons, particularly intrafamilial, and high parental expectations; (2) existential counseling facilitated the regulation of negative thoughts, strengthened awareness of personal values, and improved emotional regulation; (3) the participant became more courageous in making value-based decisions and resisting external pressures. This study highlights intrafamilial comparison as a rarely addressed factor in the literature and demonstrates the intervention’s effectiveness within only five sessions. In conclusion, existential counseling effectively helps students face life’s uncertainties with optimism, authenticity, and confidence. Practically, this approach is recommended for students facing self-confidence crises due to academic and socio-cultural pressures.